2021
DOI: 10.5406/amerjpsyc.134.2.0187
|View full text |Cite
|
Sign up to set email alerts
|

Divided Attention in Schizophrenia: A Dual Task Paradigm

Abstract: Schizophrenia is known to be associated with attentional deficits. Few studies have examined whether the disorder is also associated with a deficit in the ability to divide attention, and they have given contradictory results. Some have reported that patients show greater loss of performance than healthy controls when moving from single tasks to dual tasks, and others have reported that performance loss is similar in both groups or even that patients perform the dual task better than either task on its own. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…Regression analysis showed that attention disorders are also dependent on the onset of the disease. This observation of ours confirms the conclusion of other authors that attention is a factor associated with the severity of the schizophrenia process, and is an essential marker for the therapeutic dynamics and prognosis of the disease [55,56,92]. These results pose the question of searching for more complex therapeutic interventions in the treatment of patients [93].…”
Section: Discussionsupporting
confidence: 91%
“…Regression analysis showed that attention disorders are also dependent on the onset of the disease. This observation of ours confirms the conclusion of other authors that attention is a factor associated with the severity of the schizophrenia process, and is an essential marker for the therapeutic dynamics and prognosis of the disease [55,56,92]. These results pose the question of searching for more complex therapeutic interventions in the treatment of patients [93].…”
Section: Discussionsupporting
confidence: 91%